CODESRIA Bulletin Online, No. 2, February 2024 - Paulin Hountondji on African Philosophy - Diagne, Souleymane Bachir (CODESRIA Bulletin, 2024)
In 1977, a book entitled Sur la “philosophie africaine”: Critique de l’ethnophilosophie was published by Maspero, in its ‘Textes à l’appui’ collection. The book immediately became a resounding success and has been declared one of the 100 most influential African books of the twentieth century. Its author, Paulin Jidenu Hountondji, passed away in his native country, Benin, on Friday, 2 February 2024. He was almost 82. As a student of the École Normale Supérieure (Rue d’Ulm, Paris), Paulin Hountondji devoted his initial research to the work of Edmund Husserl, the subject of his Doctorat d’État. He returned to Africa, first teaching in the Congo before joining the National University of Benin, in Cotonou, where he became Professor of Philosophy. In 1995, at the Cheikh Anta Diop University of Dakar, Hountondji defended a thesis based on his work. He was engaged in a struggle (citing the title of his intellectual autobiography, The Struggle for Meaning: Reflections on Philosophy, Culture and Democracy in Africa, 2002), for the very meaning of the term ‘African philosophy’. The quotation marks in the title of his major work, Sur la “philosophie Africaine”, can be explained as follows: their purpose was to question the uses made of the notion of ‘African philosophy’. To speak about ‘African philosophy’ at that time was far from straightforward. Firstly, was philosophical thought not the prerogative of Europe alone, thus defining what made this province of the world both universal and exceptional? And, secondly, could we imagine that a thought with philosophical quality would be born on the African continent, on which Hegel rendered the verdict that its massive geography made it almost impenetrable, locking it in the Night of the Spirit? In the middle of the colonial period, a Franciscan missionary priest dared use the term in his book published in 1945, La Philosophie bantoue. The title alone appeared provocative. It was not about the ‘worldview’ of the Bantu, nor the Bantu ‘mentality’(which were at the time recognised terms), nor the neutral concept, ‘wisdom’. It addressed ‘philosophy’—that is to say, a set of ontological propositions identifiable as such, organised in a rational system and therefore corresponding to what Leibniz presented as the philosophical question par excellence: ‘Why is there something rather than nothing?’. The Franciscan priest presented to the world the ontology manifested, according to him, by the cosmol¬ogy, rituals, political organisation, arts and_first and_foremost_Languages of the Bantu, among whom he had lived for several years. His name was Reverend Father Placide Tempels. When the book was first published in French, and in English in 1959, many greeted it with enthusiasm. They saw in it, of course, not the origin of ‘African philosophy’ (which can be traced back to ancient Egypt), but the start of its identification, in the sense that La Philosophie bantoue established a pattern for works that could refer to ‘African philosophy’ or a philosophy associated with any people of the continent. Specifically, the criticism Paulin Hountondji made against La Philosophie bantoue features in articles he began publishing at the end of the sixties and which he subsequently put together in his 1977 book. It is encapsulated by the following words: a people do not philosophise. Philosophical reflection is the business of a subject who takes responsibility for the assertions he or she makes and the arguments used to defend them. To speak of ‘Bantu philosophy’ as something collective and implicit in the culture or language of the Bantu is simply to extend an ethnological statement into an ‘ethnophilosophy’. Hountondji did not invent the word, but he constructed the concept. ‘Criticising ethnophilosophy’ – to paraphrase the subtitle of his first book – the disciple of Georges Canguilhem helped to ensure that African philosophy (that is, African presence in any important philosophical question and the construction by the continent’s thinkers of concepts in African languages and in the languages of Africa that English, Portuguese or French have become, to engage with African challenges and formulate them) remains a critical tradition of the African production and discussion of assertions that self-proclaim universality and validity. And if the resources of languages and cultures are mobilised in such a construction, the result should not be a naive ethnophilosophy. The works by Paulin Hountondji on ‘endogenous knowledge’ in Africa illustrate what such an approach must be: demanding, argued and aimed at the universal. The book by Placide Tempels can be considered the commencement of African philosophy, in the sense indicated above. It i a simple fact of history. The work of Paulin Hountondji established a recommencement.